1983
DOI: 10.2337/diacare.6.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytotic Activity of Monocytes from Diabetic Patients

Abstract: The phagocytotic activity of monocytes from diabetic patients and healthy controls was studied. It was found that the number of phagocytizing cells from diabetic patients was significantly reduced in comparison with that from control individuals. However, the number of bacteria phagocytized per cell was similar in both groups. Plasma from healthy controls added to diabetic monocytes did not cause any significant change in their phagocytotic capacity. Addition of insulin to the plasma of diabetic patients faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…with diabetes is altered, resulting in a decreased bactericidal capacity of the cells and an increased susceptibility to infections. It has been shown that the number of phagocytes from these patients is significantly reduced in comparison with that from healthy individuals (Katz et al, 1983). However, the number of bacteria phagocytosed per each individual cell was similar in individuals of both groups.…”
Section: Certain Conditions Affectingmentioning
confidence: 90%
“…with diabetes is altered, resulting in a decreased bactericidal capacity of the cells and an increased susceptibility to infections. It has been shown that the number of phagocytes from these patients is significantly reduced in comparison with that from healthy individuals (Katz et al, 1983). However, the number of bacteria phagocytosed per each individual cell was similar in individuals of both groups.…”
Section: Certain Conditions Affectingmentioning
confidence: 90%
“…A likely common denominator in all these abnormalities is the dysfunction of the macrophage system. Numerous phenotypic abnormalities, including altered metabolism (9-13), aberrations in chemotactic response (12)(13)(14), phagocytosis (12,15,16), antigen presentation (17)(18)(19), receptor functions (20,21), and cytokine release (18,(22)(23)(24)(25)(26)(27) have indeed been found in peripheral blood mononuclear cells from both type 1 and type 2 diabetic patients. On the other hand, data on the function of tissue macrophages in human diabetes are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, monocytes with impaired chemotaxis 24 and phagocytosis 25 are also found in diabetic patients. We found an increased subpopulation of mononuclear cells and neutrophils both in adipose tissue and in systemic circulation.…”
Section: Foreign Body-induced Insulin Resistance H-t Wu Et Almentioning
confidence: 99%